The Digital Ruble as an innovation of Russian Law and its place in the system of objects of civil rights - D. D. Stukalova; V. A. Gaivoronskaya (Теоретическая и прикладная юриспруденция)
This article is devoted to the issues of determining the legal essence of the digital ruble as a completely new, and therefore not fully regulated and studied phenomenon. To answer these questions, the author conducts a comparative analysis of the digital ruble with various legal categories: digital currency, objects of civil rights, digital rights. In the process of comparing these concepts, the author comes to the conclusion that the digital ruble by its nature and legal characteristics is both an independent object of civil rights and digital law. In this regard, the issue of the need for detailed regulation of this very ambiguous and complex legal category is currently very acute.The purpose of this article is to determine the place of the digital ruble in the system of civil rights. To achieve this goal, the work used methods of analysis, synthesis, analogy, generalization and abstraction.